Long-term zero tillage with residue retention boosts yield, enhances energy efficiency, and mitigates greenhouse gas emissions in the western Indo-Gangetic rice–wheat systems - Chaudhary, Ved Prakash; Sawant, Chetankumar Prakash; Gupta, Ajita; Gautam, Rahul; Khadatkar, Abhijit; Magar, Ajit Pralhad; Wakchaure, Goraksha C.; Kumar, Vijay; Chaudhary, Rahul (Frontiers in Sustainable Food Systems, 2025)
The rice–wheat cropping system (RWCS) in the Indo-Gangetic Plains (IGP) of India is a dominant food production model, but its conventional management practices, viz., puddled transplanted rice (PTR) and conventionally tilled wheat (CTW), are highly energy-intensive, leading to excessive greenhouse gas (GHG) emissions, lower energy use efficiency (EUE), and soil degradation. This 15-year field study, using a split–split plot design, evaluated the impact of various crop establishment methods on crop productivity, energy use, carbon indices, and GHG emissions under RWCS. Conservation agriculture (CA)-based practices such as zero-till direct-seeded rice (ZTDSR), dry-seeded rice (DSDSR), and zero-till wheat (ZTW) and wheat sown with a Turbo Happy Seeder with residue retention (THSW + R) were compared with conventional systems. The results showed that ZTDSR and THSW + R significantly reduced total input energy, fossil fuel use, and irrigation water demand, resulting in 14–21% energy savings compared to PTR-CTW systems. ZTDSR-THSW + R emerged as the most energy-efficient combination, recording the highest EUE (13.6) and the lowest system-specific grain energy (9.5 MJ kg−1), reducing global warming potential by over 50%. Despite slightly lower rice yields under ZTDSR, system productivity remained comparable due to superior wheat performance. Carbon output (8,907 kg C ha−1) and carbon efficiency ratio (11.43) were higher under CA-based treatments for wheat due to greater biomass returns and reduced carbon inputs (2,293 kg C ha−1). Integrating zero-till and residue management practices in RWCS enhances energy efficiency, improves sustainability metrics, and reduces environmental footprints. These findings support a transition from conventional to CA-based systems for climate-resilient, resource-efficient agriculture in the IGP and similar agroclimatic zones.